Morphological and molecular identification of Toxocara isolated from road-killed golden jackals in Northern Iran - Amirhosain Roohi Koshalshah; Meysam Sharifdini; Mohammad Saleh Bahreini; Amir Masoud Salemi; Syed Mohammad Kifayatullah Andrabi; Syeda Sadaf Mehdi; Fattaneh Mikaeili (BMC Veterinary Research)
Abstract Background Toxocariasis is caused by infection with Toxocara canis and Toxocara cati, common nematodes of canids and felids, respectively. Humans become infected after the accidental ingestion of embryonated eggs of Toxocara from the soil or the consumption of raw and undercooked meat containing Toxocara larvae. The aim of this cross-sectional study was to identify ascarid nematodes isolated from jackals in Guilan and Mazandaran provinces, based on morphological and molecular approaches. Methods This cross-sectional study was conducted on 41 road-killed golden jackals collected from Guilan and Mazandaran provinces in northern Iran. At first, species identification was carried out based on morphological characterization. Genomic DNA was extracted from the isolates of Toxocara collected from jackals. PCR-RFLP of Ribosomal DNA regions (ITS) using RsaI endonuclease enzyme and PCR-sequencing were carried out to identify Toxocara species. The sequence data were aligned using Bioedit software and compared with published sequences in GenBank using the BLAST system. Phylogenetic analysis was performed using MEGA 5.0 software. Results Eleven out of 41 road-killed golden jackals (26.8%) were infected with Toxocara nematodes. All the isolates were confirmed as T. canis based on morphological and molecular methods. A pairwise comparison of the sequences did not show any differences in nucleotide sequences within T. canis isolates, and the sequences were identical and exhibited 100% homology. Conclusions Considering the almost high prevalence of T. canis in golden jackals and its critical role in human toxocariasis, the identification of parasite species by molecular methods can be used to plan prevention and control programs in human and animal communities. Since, the ITS sequences of T. canis isolated from jackals in Iran were utterly similar to the ITS sequences of T. canis isolated from other hosts from different areas of the world, it is hypothesized that the type of host and geographical region do not affect the genetic diversity of the ITS region sequences of T. canis.